2003
DOI: 10.1002/ccd.10548
|View full text |Cite
|
Sign up to set email alerts
|

Aortic dissection after stent dilatation for coarctation of the aorta: A case report and literature review

Abstract: A case of stenting for native coarctation is described in a 65-year-old female with a fatal dissection after implantation. The histology of the aorta in coarctation and in the elderly is described. The experience of stenting in older patients is reviewed and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 23 publications
0
50
1
1
Order By: Relevance
“…Aortic disruption can be a potentially catastrophic complication of CoA stenting (7,22,23). This complication occurred in one of the 45 patients in our study; however, deployment of a second covered stent successfully excluded the area of disruption from the circulation.…”
Section: Discussionmentioning
confidence: 70%
“…Aortic disruption can be a potentially catastrophic complication of CoA stenting (7,22,23). This complication occurred in one of the 45 patients in our study; however, deployment of a second covered stent successfully excluded the area of disruption from the circulation.…”
Section: Discussionmentioning
confidence: 70%
“…18,19 Although rare, aortic rupture and dissection have been reported during stenting for adult CoA. 14,20,21 For this reason, covered aortic stents should always be available when by guest on May 11, 2018 http://circinterventions.ahajournals.org/ Downloaded from Uncovered Self-Expandable Stent CoA treating these patients, 22,23 as reported in our experience. Literature data indicate that an aggressive balloon angioplasty of the native aorta and repeated dilatations of the stent contribute to the overall risk of iatrogenic aortic wall damage.…”
Section: Procedural Safetymentioning
confidence: 69%
“…10 Some complications including balloon rupture, stent migration and aneurysm formation caused by stent implantation have been reported and those may be related to using over enlarged balloons. 8,11,12 The current data suggest that the diameter of DAo may not always be a proper gauge to determine the size for catheter enlargement. Nielsen et al reported that the narrowest aortic CSA indexed to the BSA using magnetic resonance imaging is a more reliable marker for detecting significant CoA (pressure gradients >20 mmHg).…”
Section: Circulation Journal Vol72 December 2008mentioning
confidence: 81%